Simulasi Komputasional untuk Meningkatkan Efisiensi DSSC Berbasis TiO₂/Cu: Studi Ketebalan dan Suhu Fotoanoda - Yuyun Setyawati; Edy Supriyanto; Moh. Nawafil; Agus Subekti (Postgraduate, University of Mataram, 2025)
In order to address the growing energy demands in Indonesia, this study investigates the enhancement of TiO₂/Cu-based Dye-Sensitized Solar Cells (DSSCs) efficiency through computational simulation. The research focuses on the influence of photoanode thickness and operational temperature on the device’s performance. The simulation results revealed that an optimal photoanode thickness of 2.60 μm achieved the highest efficiency of 8.493%, balancing light absorption and electron transport. Additionally, an operational temperature of 350 K was found to yield the maximum efficiency of 9.376%, as higher temperatures reduce electrolyte viscosity, improve ion mobility, and minimize charge recombination. Validation of the simulation model was conducted by comparing it with experimental data from prior studies, ensuring its reliability in representing charge transport phenomena in DSSCs. These findings offer crucial insights for designing cost-effective, efficient, and sustainable DSSCs suitable for Indonesia’s abundant solar energy resources. Further research is recommended to explore the interaction of additional components and external factors to enable commercial scalability of this technology.